Cyberfeminisme dan Pemberdayaan Perempuan Melalui Media Baru - Salim Alatas; Vinnawaty Sutanto (Institut Pertanian Bogor, 2019)
In the era of new media, every individual and social, cultural, economic and political groups must require themselves to interact actively with new media. This is done not only to express the identity of individuals or groups, but more importantly how then each group uses new media as a means of communication to empower or liberate themselves. Feminism as a liberation movement for women has included new media and their application as important issues in their movements; cyberfeminism is an important outcome of this application. New media in the view of cyberfeminism has provided a large area, a region with an arena of objectives of cyber space, namely a process of technology that is rendered, by empowering women through techno-culture. Cyberfemists argue that women are naturally suitable for using new media. Cyberfemists also make efforts to work towards empowering women through new media by fighting various male-dominated discourses that surround technology use. This paper generally wants to discuss the concept of